2017
DOI: 10.3390/toxins9040134
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in Helicobacter pylori-Induced Gastric Cancer

Abstract: Persistent infections with the human pathogen and class-I carcinogen Helicobacter pylori (H. pylori) are closely associated with the development of acute and chronic gastritis, ulceration, gastric adenocarcinoma and lymphoma of the mucosa-associated lymphoid tissue (MALT) system. Disruption and depolarization of the epithelium is a hallmark of H. pylori-associated disorders and requires extensive modulation of epithelial cell surface structures. Hence, the complex network of controlled proteolysis which facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 148 publications
(211 reference statements)
1
21
0
Order By: Relevance
“…In addition, intermediate filament, brain development, proteolysis, negative regulation of endopeptidase activity, keratinocyte differentiation, and peptide cross-linking were predominantly dysfunctional molecular function. As the most significant difference was proteolysis, it is reasonable to infer that Hp actively interferes with host cells by activating cellular proteases and the secretion of bacterial proteases, which has also been reported before 17. As for the pathway, the results suggested that cancer-related pathway 'PI3K-Akt signaling pathway' has the most significant difference.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, intermediate filament, brain development, proteolysis, negative regulation of endopeptidase activity, keratinocyte differentiation, and peptide cross-linking were predominantly dysfunctional molecular function. As the most significant difference was proteolysis, it is reasonable to infer that Hp actively interferes with host cells by activating cellular proteases and the secretion of bacterial proteases, which has also been reported before 17. As for the pathway, the results suggested that cancer-related pathway 'PI3K-Akt signaling pathway' has the most significant difference.…”
Section: Discussionsupporting
confidence: 59%
“…Hp‐I is related to peptic ulcer disease development. Moreover, long‐standing Hp ‐associated gastritis predisposes to gastric adenocarcinoma and mucosa‐associated lymphoid tissue (MALT) lymphoma development . It is established knowledge nowadays, that microbes and their products are able beyond the local induced inflammation, to orchestrate and shape the character of immune system as well as promote or even inhibit tumorigenesis .…”
Section: Introductionmentioning
confidence: 99%
“…In many bacterial pathogens, HtrA proteases are widely conserved and play an important role in the virulence and survival of microbes under stress conditions ( Hoy et al, 2013 ; Backert et al, 2017 ; Posselt et al, 2017 ; Skorko-Glonek et al, 2017 ). In addition to the protease function, HtrA acts as a chaperone being responsible for protein quality control and degradation of misfolded proteins in the periplasm ( Kim and Kim, 2005 ; Hoy et al, 2013 ), suggesting that HtrA is highly active under harsh conditions ( Hoy et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%